Different surgical approaches for the management of periodontal intrabony defects in the anterior maxilla - Ninad Milind Padhye; Amruta Arun Joshi; Aanchal Mahendra Agrawal (Wolters Kluwer Medknow Publications, 2018)
This article reports the outcomes of judicious management of periodontal intrabony defects in the anterior maxilla with a long-term follow-up. Two cases reported with a deep probing pocket depth along with an osseous defect due to chronic periodontitis. After completion of nonsurgical periodontal and endodontal therapy, guided tissue regeneration was undertaken for both the cases. Freeze-dried bone allograft along with a biphasic cross-linked collagen membrane was used in the osseos defect. The patients were then recalled for professional scaling on a regular basis. The long-term follow-up of both the cases showed a resolution of the probing pocket depth and radiographic evidence of bone fill in the osseous defect with stable results.